Commodity Market Prices and Its Impact on Exchange Rate of Pakistan - ASAD SARFARAZ KHAN; DR. SHAKIL IQBAL AWAN; DR. SYED ABDUL MOIZ (Journal of Business & Tourism, 2021)
Pakistan’s economy and exchange rate has experienced many ups and downs in the last ten years. The exchange rate has depreciated from Rs.59/ to Rs.104/. This is causing a massive dent to Pakistan economy. According to the State Bank of Pakistan, Pakistan is consistently facing a current account deficit for the last several years and a depreciated currency is one of the main reasons for the deficit. This study analyzes the relationship between the commodity market prices and exchange rates in Pakistan both in long and in short run. This research utilized the monthly data for the past ten years from Jan-2006 to Dec-2015. The results are quite surprising because in Pakistan, none of the prices of the commodities (i-e oil and gold) have short term relationship with the exchange rate of Pakistan. This study also does not find any long-term relationship among the variables.